Who supports democracy? Evidence from a survey of Chinese students and scholars in the United States. Issue 4 (6th June 2016) - Han, Donglin; Chen, Dingding
Abstract : Does the experience of living in the United States lead Chinese people to believe that China should pursue democracy? Our study produced mixed results, as we found that overseas study resulted in significant attitude changes by various means. Education in social sciences and consumption of foreign media were both associated with supportive attitudes toward democracy, and also led respondents to believe that Western liberal democracy is a good thing and to push for it. Conversely, living overseas had a negative effect on respondents' support for Chinese democratization, as the longer they had lived in the United States, the better they understood Western democracy and were suspicious about whether China should pursue immediate democratization. Meanwhile, we also find Chinese media has a negative impact on public support for democracy, both instrumental and intrinsic. Finally, factors associated with attitudes toward democracy, such as traditional values, self-expression values, and perceived performance of the Chinese government, were also significant.